Heterogeneity in Involvement in School Bullying: A Latent Classes Analysis - Mellado, Carlos (2021)
The present study aimed to develop a typology of school bullying through a statistical technique that minimizes the classification error in groups. This typology allows examining how multiple attributes of bullying coexist in people without artificially separating those attributes. Using a latent class analysis, six items that represented the role of the witness, the victim, and the aggressor were modeled in school bullying situations in a sample of 440 Chilean schoolchildren between 14 and 20 years of age (M = 16,30 and SD = 1,42). Two models are reported with four and five latent classes, respectively. In the four-class model, it can be seen a group called “Not Involved” (14,5%) which has not been implicated in any of the roles of harassment; another group called “Witness” (56,2%) which has only been involved as a witness in bullying situations; a group called “Witness and Victim” (13,3%) which has been involved as a witness and victim in school bullying situations; and finally, a group called “Witness, Victim and Aggressor” (16%) which has been involved in all roles. In the five-class model, the same groups are observed, plus one denominated as “Witness and Aggressor” implicated as a witness and aggressor in school bullying situations. The results show that most of the student body has been involved in bullying situations and that an important part has been involved in more than one role, which implies that victimization and perpetration of bullying are not mutually exclusive.